INSTALLATION AND CONFIGURATION OF AN IONOSPHERIC SCINTILLATION MONITORING STATION BASED ON GNSS SDR RECEIVERS IN BRAZIL - Linty, Nicola; Correia, Emilia; Hunstad, Ingrid; Kudaka, Amauri S. (Revista Mackenzie de Engenharia e Computação, 2018)
The use of Global Navigation Satellite Systems (GNSSs) is nowadays very popular, and the positioning service that they provide is becoming the basis of several applications. Due to their wide coverage, GNSS signals can be used at no cost as probing signals to retrieve parameters to characterize the atmosphere, such as ionospheric scintillation indexes. GNSS receivers coupled to the specific algorithm are indeed a valid alternative to large and expensive ad hoc equipment such as ionosondes. In particular, Software Defined Radio (SDR) receivers are characterized by a higher level of flexibility and configurability when compared to commercial receivers, which fits for the purposes of ionospheric monitoring and enable the study of advanced and innovative algorithms, both for scientific purposes (ionospheric monitoring, space weather), and for technological development (robust GNSS receivers design). A GNSS-based ionosphere monitoring station, including an SDR-based receiver and a professional receiver, was installed in the CRAAM laboratory at Mackenzie Presbyterian University (São Paulo, Brazil) on May 2017. Details of the installation and the new approaches for the storage, processing, and transfer of GNSS data, including raw Intermediate Frequency (IF) samples, are described, along with preliminary results related to ionospheric events captured during the first months of its operation.